2012
DOI: 10.5194/acp-12-3189-2012
|View full text |Cite
|
Sign up to set email alerts
|

One decade of parallel fine (PM<sub>2.5</sub>) and coarse (PM<sub>10</sub>–PM<sub>2.5</sub>) particulate matter measurements in Europe: trends and variability

Abstract: Abstract. The trends and variability of PM10, PM2.5 and PMcoarse concentrations at seven urban and rural background stations in five European countries for the period between 1998 and 2010 were investigated. Collocated or nearby PM measurements and meteorological observations were used in order to construct Generalized Additive Models, which model the effect of each meteorological variable on PM concentrations. In agreement with previous findings, the most important meteorological variables affecting PM concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
111
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(131 citation statements)
references
References 46 publications
19
111
0
1
Order By: Relevance
“…The correlation between SO2 and wind speed is negative. On the other hand, as it was expected, the relationship between SO2 and temperature is positive (Barmpadimos et al, 2012;Lecoeur et al, 2012). Similarly, the relationship between recycling rates and temperature is negative, while the association of recycling rates and wind speed is positive.…”
Section: Datamentioning
confidence: 51%
“…The correlation between SO2 and wind speed is negative. On the other hand, as it was expected, the relationship between SO2 and temperature is positive (Barmpadimos et al, 2012;Lecoeur et al, 2012). Similarly, the relationship between recycling rates and temperature is negative, while the association of recycling rates and wind speed is positive.…”
Section: Datamentioning
confidence: 51%
“…A similar interpretation, can also be given for the temperature, as decreases in temperature, which may be associated with cold weather, high wind speed or with high levels of rainfall, lead to traffic reduction and thus to air quality improvement. On the other hand, temperature, may increase pollution, especially, for O 3 , since is formed under sunlight, associated with high levels of solar radiation and temperature (Brook et al, 1993;Tai et al, 2010;Han et al, 2011;Barmpadimos et al, 2012;Kim et al, 2014;Zhang et al, 2015). However, the coefficient of the average temperature was found significant and positive only in the case of CO and O 3 .…”
Section: Regression Estimatesmentioning
confidence: 64%
“…In a study by Rosenfeld et al (2008) pollution may increase or decrease precipitation depending on other environmental factors, indicating that the relationship is not still clear. Overall, a positive relation between maximum and average temperature and air pollution is documented in earlier studies, while a negative relationship between minimum temperature and wind speed is found (Roberts, 2004;Tai et al, 2010Tai et al, , 2012Barmpadimos et al, 2012;Lecoeur et al, 2012;Zhou et al, 2014;Price et al, 2014).…”
Section: Summary Statisticsmentioning
confidence: 81%
See 2 more Smart Citations